Do Diacritical Marks Play a Role at the Early Stages of Word Recognition in Arabic? - Perea, Manuel; Abu Mallouh, Reem; Mohammed, Ahmed; Khalifa, Batoul; Carreiras, Manuel (Frontiers in Psychology, 2016)
A crucial question in the area of visual-word recognition is whether visual-letter similarity plays a role at the early stages of word processing. Here we focused in Arabic because there are various groups of letters that share the same basic shape and only differ in the number/location of diacritical points. We conducted a masked priming lexical decision experiment in which a target word was preceded by: i) an identity prime; ii) a prime in which the critical letter was replaced by a letter with the same shape that differed in the number of diacritics (e.g., صخفية – صحفية); or iii) a prime in which the critical letter was replaced by a letter with different shape (e.g., صكفية – صحفية). Results showed a sizable advantage of the identity condition over the two substituted-letter priming conditions (i.e., diacritical information is rapidly processed). Thus, diacritical marks should play an essential role in the “feature letter” level of models of visual-word recognition in Arabic.